Analisis terhadap Putusan Pengadilan Agama Sawahlunto Nomor 25/Pdt.P/2025/PA.SWL tentang Dispensasi Kawin Hamil di Luar Nikah karena Alasan Mendesak Perspektif Mashlahah Mursalah - Diva Chairunisa Ridwan; Rahmiati (AHKAM, 2026)
Although marriage dispensation has been widely examined in Islamic family law research, studies specifically analysing judges’ considerations in marriage dispensation cases involving pregnancy outside marriage from the perspective of maṣlaḥah mursalah remain limited, particularly regarding Sawahlunto Religious Court Decision Number 25/Pdt.P/2025/PA.SWL. This study aimed to analyse the judge’s considerations in granting a marriage dispensation application due to pregnancy outside marriage as an urgent reason and to assess the conformity of these considerations with the principle of maṣlaḥah mursalah. This study employed a qualitative approach with a case study design and field research. The research informant was a judge of the Sawahlunto Religious Court selected using purposive sampling. Data were collected through observations, semi-structured interviews, and a documentation study of the court decision and were subsequently analysed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the judge’s considerations were based on positive law provisions, facts presented during the proceedings, evidence, and the circumstances of the applicants. Pregnancy outside marriage was regarded as an urgent reason to prevent greater harm. From the perspective of maṣlaḥah mursalah, the decision was oriented towards protecting lineage and honour and ensuring legal certainty for the parties. This study confirms that the application of maṣlaḥah mursalah can serve as a substantive basis for considering benefits and preventing harm in marriage dispensation cases. These findings provide a theoretical contribution to the development of Islamic Family Law studies and practical implications for Religious Court judges in formulating legal considerations oriented towards protecting the parties. Future research may conduct comparative studies of marriage dispensation decisions across different Religious Courts.